Os velhos curtumeiros da cidade de Franca - SP: trabalho e experiência 1940-1980 - Ferreira Filho, Aurelino José (2007)
The purpose of this work is become experiences of life and work of a group of men, the old men that work in tannery at the Franca City between 1940 and 1980. Men who in this period left small cities of south of Minas Gerais looking for better conditions of life and in the Franca city, northeast region of São Paulo. There was a reflection about the social displacement of these men, the work in the coffee plantation in the São Paulo region, the work at the tannery and the preparation of de tannery workers office as a promising way to understand experiences of life of these men, that before work in this position tried another works and gains between the field and the city. It is relevant to say that the itinerancy of the work practice in the learning of the work and in the formation of their lives at the city. Understanding that for these men become workers, to can a urban work, to be part of a category of work needed a dialog, always anxious, with processes that do not apart personal life, the relation with the work and the places where their lives grew up, the field and the city, what mean find them at the layer of social formation and economic of the city int that time, in the invisibility given to the common workers, poor and migrants in general in a city that look for the paulistas `face of urbanity and modernization in that moment. This is in their memories, showing aspects of their lives, noticing how they feeling observing apart from them, in question of time, space and social experiences of work that were true references in their lives. There was interest in understand their comprehension of their own way, how they look to themselves, in that process , that in a special moment, change them in urban workers to after exclude them of the productive process. Noticing them in a way that they situated themselves in the present time, how they are in this process, the problems, the reminder and things that they left in the past